Pengembangan Video Materi Sistem Pencernaan Untuk Meningkatkan Hasil Belajar Siswa Kelas VIII SMP Kristen Baithani Tosari - Veronika Indrawati; Diyah Ayu Widyaningrum (Paradigma: Jurnal Filsafat, Sains, Teknologi, dan Sosial Budaya, 2024)
Information and Communication Technology (ICT) has carried out many transformations in various fields, including education. Education today has experienced many very rapid changes to improve the quality of education. One of the things researchers do in dealing with current education is by developing videos. The development of this video was carried out at Baithani Tosari Christian Middle School in class VIII. Video development was chosen because we saw the situation that occurs in schools where schools still use the lecture method, students are sometimes lazy to pay attention and read books. In developing this video, the researcher used the Research and Development method using the 4-D model, Define, Design, Develop and Dissemine to produce a product and test the effectiveness of the product. And at the dissemination stage, classroom action research (PTK) was carried out. Video development research is used to see improvements in student learning outcomes which emphasize cognitive aspects. And from the results of research conducted in two cycles, good changes occurred after the development of this video. Where the data obtained from the pre-action test results was 8.7% in cycle I, increasing to 34.8% and in cycle II increasing to 87%. Thus, the development of videos on digestive system material can improve student learning outcomes at Baithani Tosari Christian Middle School.